An exploration of the role of adult literacy in community development : a comparative study of perceptions and experiences in Juaso and Saaman in Ghana - Nkansah, Theophilus (School of Education, 2016)
This study explored the relationship between adult literacy and community development in Ghana from a social practices perspective of literacy and people- centred development. The study adopted an interpretive qualitative case study methodology, using the perceptions and experiences of research participants in two neighbouring communities. Primary data were collected using four ethnographic methods of data collection namely: in-depth interviews, participant observation, informal conversations, and document review. The data was then analysed using the constant comparative method. Consistent with the claims of the social practice theory of literacy, the study found many social uses of literacy, as well as literacy practices among the learners. It also identified many community-wide literacy practices. These included commercial literacy, religious literacy, funeral literacy, and public communications literacy. The study established that in both communities, adult literacy, in terms of participation in adult literacy classes, or the social uses of literacy by learners, did not lead to community development. However, some of the general literacy practices like reading and writing, funeral literacy, and public communications literacy played roles in the implementation of community development. Development committees, for instance, used reading and writing in activities like ii taking minutes at committee meetings, writing letters to donors for support, and collecting levies.